The permanently rotating wind turbines: a new strategy for reliable power system frequency support under low and no wind conditions - Kristina Džodić; Željko Đurišić (Frontiers in Energy Research, 2023)
The problem of frequency stability becomes more concerning as the presence of converter-interfaced units increases and conventional generators are suppressed. A decrease in total system inertia, inherently delivered by synchronous generators, results in abrupt frequency changes and jeopardizes power system stability. Therefore, securing sufficient flexible resources with frequency support capability is necessary. The rotational masses of wind turbines (WTs) are a significant and economical source of flexibility in power systems. However, the available kinetic energy (KE) of the WTs’ rotational masses depends on wind conditions and can only be exploited when the wind speed is sufficient for their rotation. When the wind speed is low, the WT is stopped and cannot support the frequency recovery. In this paper, a new concept of WT operation is proposed, which enables the permanent rotation of the WT under low and no wind conditions, making them reliable flexible resources that can continuously provide frequency support. Due to its widespread presence, the doubly-fed induction generator (DFIG) type of machine was considered. The variable-speed WT’s converter management allows rotational speed control, fast power injection, and release of the turbine’s stored KE even when no wind energy is available. The estimated accessible KE in the WT justifies the proposed concept, and the energy consumption due to motoring operation under low and no wind conditions is shown to be acceptable. A case study is performed for the South Banat region in Serbia to demonstrate the presented management concept. Additionally, a dynamic simulation was implemented to illustrate the permanent operation strategy’s impact on frequency stability in a low-inertia system under low and no wind conditions. Besides virtual inertia continuous capability, the proposed concept provides reduced wear of the WT mechanical components due to a lower number of on/off events.